Expressions of dissatisfaction and complaint by people with learning disabilities: A discourse analytic study. (27th September 2011) - Jingree, Treena; Finlay, W.M.L.
<x xml:space="preserve">Abstract</x> This paper uses critical discursive psychology to examine expressions of dissatisfaction and complaint by people with learning disabilities. UK government policies stress that people with learning disabilities should have more control over their lives. Expressing dissatisfaction about services is an important aspect of this process. However, given that such individuals are often treated as incompetent, and given the delicate nature of complaining about services one might rely on for day‐to‐day support, this can be difficult to do. In building complaints, speakers drew on repertoires about competence and incompetence, the right to free choice as a principle, and tempered dissatisfaction to make contrasts between good and bad supporters and practice. While the complaints show many of the general features of complaints identified in previous work in the general population, they were crafted to the particular institutional context of social care, and attended both explicitly and implicitly to the particular issues of competence, power, and authority found in those services. Speakers positioned themselves as competent, and service workers as more or less competent in their roles. Issues of power in social care services were observed explicitly in the accounts, whereby people described staff as controlling and it being difficult to voice dissatisfaction. They were also implicit in the way speakers drew on the others with institutional authority for corroboration and comparison.